The working culture of local bank vs foreign bank (a case study of Rhb Bank Berhad & Deutsche Bank (M) Berhad) / Sue Anna Janif (Faculty of Business and Management, 2007)
The purpose of this research is to study "The Working Culture of Local Bank vs. Foreign Bank (A Case Study of RHB Bank Berhad and Deutsche Bank (M) Berhad )". The employees of RHB Bank and Deutsche Bank have been selected randomly and the sample size is 40 for each of organization. Thus, make it total of 80 sample size. The objective of the study is to see whether the power distance culture existed between senior staff and other staff in each of these banking institution, to know are the employees in each banking institution is willing to take risk (uncertainty avoidance), to explore whether the employees in each banking institution by nature collectivism or individualism, and to study the employees in each banking institution are by nature masculinity or femininity. In this research, the researcher is using frequency analysis and cross-tabulation in order to help finalize the data from questionnaires. From findings the researcher finds that in local bank (RHB Bank), power distance between superior and subordinates is not exist, the employees are not willing to take risk, they are also more collectivism rather than individualism, and the employees are strongly femininity. While in foreign bank (Deutsche Bank), there are some power distance exist, the employees are willing to take risk, they are also more collectivism rather than individualism, and the employees are strongly masculinity.